Human Subjects Research and Quality Improvement Projects: What's the Difference? - Varnadoe, Christa; Johnson, Kathryn (AJN American Journal of Nursing, 2025)
Editor's note: This is the 26th article in a series on clinical research by nurses coordinated by the Heilbrunn Family Center for Research Nursing at Rockefeller University. The series is designed to be used as a resource for nurses to understand the concepts and principles essential to research. Each column will present the concepts that underpin evidence-based practice—from research design to data interpretation. To see all the articles in the series, go to https://links.lww.com/AJN/A204. This article, one in a series on clinical research by nurses, defines human subjects research and quality improvement projects, describes their key differences, and identifies ways to determine when their use is appropriate in projects undertaken by nurses.